The political dimension in architecture and the mutual impact between them to highlight the political identity of architectural work (Arab and international) - حسين هلا (Latakia University Journal -Engineering Sciences Series, 2025)
Throughout history, architecture has expressed the prestige of the state through the construction of palaces, parliaments, courts, and other political buildings. Architecture has always contributed to highlighting the political identity of the state. This correlation can be felt in the experience of the city that was formed as a result of political decisions. The presence of one or more buildings cannot express political identity, but rather goes beyond that to the concept of similarity in all cities in one country, which makes them have one identity. The research aims to clarify dimensions of architecture and the impact between them, the great correlation between architecture and politics in architectural projects. The state made and went for its political passport through architecture as a political witness, in which architecture is a record of the political events that it has experienced, the political symbolism of architecture. : It represents one aspect of the state’s strength and political orientations. I took a study of the currents of political and economic events that lead to the formation of the architecture of cities. An Arab and international case study of political influences in architecture was carried out. Since the emergence of cities, there has been a clear connection between political trends and architecture (the influence of politics on architecture), as the city has always been an image of the government system.